1988
DOI: 10.1128/aem.54.2.466-472.1988
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Veratryl Alcohol and Hydrogen Peroxide on Ligninase Activity and Ligninase Production by Phanerochaete chrysosporium

Abstract: Veratryl alcohol, added as a supplement to cultures of Phanerochaete chrysosporium, enhanced ligninase activity through protection of the ligninase against inactivation by hydrogen peroxide produced by this fungus in cultures. In the presence of veratryl alcohol, the loss of ligninase activity observed in non-proteinsynthesizing cultures (cycloheximide-treated) equaled the extracellular protein turnover. When cultures were not supplemented with veratryl alcohol, inactivation of ligninase by hydrogen peroxide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 33 publications
8
49
1
Order By: Relevance
“…Similar data have been published on LiP activity of Coriolopsis gallica cultivated in the presence of Tween 80 [55]. Tonon and Odier [56] and Valli et al [57] suggested that veratryl alcohol does not stimulate higher enzyme activity by inducing de novo protein synthesis, but protects the enzyme from inactivation by excess H 2 O 2 produced by the fungus in the culture. Obviously, the effect of the widely used inducers on ligninolytic enzyme production depends on several factors and each strain responds in a particular way to each of these factors.…”
Section: Discussionsupporting
confidence: 73%
“…Similar data have been published on LiP activity of Coriolopsis gallica cultivated in the presence of Tween 80 [55]. Tonon and Odier [56] and Valli et al [57] suggested that veratryl alcohol does not stimulate higher enzyme activity by inducing de novo protein synthesis, but protects the enzyme from inactivation by excess H 2 O 2 produced by the fungus in the culture. Obviously, the effect of the widely used inducers on ligninolytic enzyme production depends on several factors and each strain responds in a particular way to each of these factors.…”
Section: Discussionsupporting
confidence: 73%
“…Considering the negative results obtained with veratryl alcohol when T. t'ersicolor was grown in the absence of humic acids, this compound seems to act as a mediator in the oxidation reactions catalysed by peroxidases [25][26][27] or as a preventive agent of enzymes from H.,O2-mediated inactivation [13,28,29] rather than as an inducer of the ligninolytic system [12,30]. In the presence of humic acids, veratryl alcohol induces an increase in peroxidase activities of both fungi, with no corresponding increase in humic acid decolorization.…”
Section: Discussionmentioning
confidence: 99%
“…intermediates [10] whereas MnP oxidizes Mn 2+ into Mn 3÷, which is the effective agent involved in the oxidation of phenolic units of lignin [11]. The effect of veratryl alcohol, known to be an enhancer of the ligninolytic system [12,13], was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic representation of the commonly accepted reaction mechanism that accounts for product formation from VA (1) is depicted in Scheme 1. LiP oxidizes VA to the corresponding radical cation (VA , 1a) which may lose a proton to form a radical that is oxidized further by LiP to VAD (2).…”
Section: Inconsistencies In the Previous Mechanismmentioning
confidence: 99%